Observasi Bakat Menggunakan Aplikasi Talents Mapping untuk Orang Tua Siswa Sekolah Alam Tangerang - Putra, Tri Dharma (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
During this pandemic, student learning activities are mostly or entirely carried out at home with their respective parents. One aspect that is evaluated by the teacher at the school periodically is the development of children's talents. Measurement/reading of children's talents during this pandemic needs to be done by parents at home. Among the applications that can be used to measure talent is the Talents Mapping application. Measurement of talent with Talents Mapping aims to ensure that students have carried out 114 productive activities so that the traits and productive roles that most often appear as indicators of their talents can be identified. Andry Fadjriya has developed a method of observing children's talents (Talents Observation) which is derived from the Talents Mapping application so that it can be used for elementary school students. This training aims to provide the ability to observe talent for the parents of Tangerang Alam School students so that they are able to identify the talents of their respective children. The Talents Mapping application generates reports covering 34 productive traits, 114 productive activities, and productive roles. So this training was carried out for 5 sessions @ 2 hours in order to provide a complete understanding to the parents of the Tangerang Alam School students.